2012
DOI: 10.1902/jop.2011.110230
|View full text |Cite
|
Sign up to set email alerts
|

Response to Periodontal Therapy in Patients Who Had Weight Loss After Bariatric Surgery and Obese Counterparts: A Pilot Study

Abstract: An improved response to non-surgical periodontal therapy is observed in obese patients who had significant weight loss after BS compared with obese patients who did not have such a surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 35 publications
5
42
0
9
Order By: Relevance
“…A hyper-inflammatory state was [table/ Fig-4]: Diet chart prescribed for patients treated by bariatric surgery proposed as a mechanism to explain this association. In our study we tried to reprove this theory, we found that post surgically the patients showed a decreased body mass index and along with this also demonstrated decrease in PI and bleeding on probing which is in accordance with Lakkis et al, who found that those patients who had lost significant weight after bariatric surgery showed improved response to non surgical periodontal therapy compared to those who did not undergo bariatric surgery and had not lost weight by non surgical treatment modalities [10].…”
Section: Discussionsupporting
confidence: 86%
“…A hyper-inflammatory state was [table/ Fig-4]: Diet chart prescribed for patients treated by bariatric surgery proposed as a mechanism to explain this association. In our study we tried to reprove this theory, we found that post surgically the patients showed a decreased body mass index and along with this also demonstrated decrease in PI and bleeding on probing which is in accordance with Lakkis et al, who found that those patients who had lost significant weight after bariatric surgery showed improved response to non surgical periodontal therapy compared to those who did not undergo bariatric surgery and had not lost weight by non surgical treatment modalities [10].…”
Section: Discussionsupporting
confidence: 86%
“…Several studies (23)(24)(25)(26)(27) have examined periodontal outcomes after nonsurgical periodontal treatment (NSPT) for CP in obese patients. Although some studies reported that obesity did not affect clinical attachment gain or probing pocket depth (PPD) reduction after periodontal treatment (25,26,28), other studies showed that patients with a higher body mass index (BMI) had a poorer response to NSPT (19,24).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies reported that obesity did not affect clinical attachment gain or probing pocket depth (PPD) reduction after periodontal treatment (25,26,28), other studies showed that patients with a higher body mass index (BMI) had a poorer response to NSPT (19,24). It remains to be determined whether NSPT improves periodontal outcomes in obese patients (4).…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in proinflammatory cytokines secondary to weight loss may have an indirect effect on periodontal health. Lakkis et al, reported an improved response to non-surgical periodontal therapy observed in obese patients who had significant weight loss after bariatric surgery compared to obese patients who did not have such a surgery [24]. Pataro et al, also observed the differences in periodontal condition in individuals at different times of the bariatric surgery, showing a high prevalence of periodontitis in both preoperative and postoperative follow-up [25].…”
Section: Interventions In Obese Subjectsmentioning
confidence: 99%